Towards a comprehensive understanding of blockchain technology adoption in various industries in developing and emerging economies: a systematic review - Zainab Amin Al-Sulami; Nor'ashikin Ali; Rohaini Ramli; Songfeng Lu (Cogent Business & Management, 2024)
The fast growth and wide range of applications of blockchain (BC) technology in various industries is irrefutable. Generally, BC technology is still in at an infant stage but it has generated significant interests in many sectors and industries. Nonetheless, despite an uptake of interest on the application of BC technology, the extent of its adoption in various industries in many countries remains partially understood. This paper aims to assess the current status of research on adoption of BC technology in various industries, particularly in developing and emerging economies. This study systematically reviewed the applied theories and models, adoption factors considered in each study, benefits, barriers and challenges of BC adoption intention in different industries from 86 articles published in the past five years from 2019 to end of June 2023. Findings showed several popular adoption models such as the Technology Acceptance Model, Unified Theory of Acceptance and Use of Technology and Task Technology Fit in the reviewed articles. Benefits, barriers and challenges were evident from each of the industries, implying the need to further understand BC adoption and application in these industries. This review also identifies a few research gaps and provides recommendations for future researches.
Keywords: 650; Blockchain technology; acceptance; adoption; industries; developing and emerging countries